Contextual information about the Peruvian national ingroup and its effect on attitudes towards a novel brand - Nightingale Ferrer, Ian (2018)
The effect of contextual information about the national ingroup on explicit and implicit attitudes towards a novel brand was studied on a sample of university students from the Lima Metropolitana area (n = 59). The results show that the negative information about the ingroup exerts more influence on explicit attitudes towards a novel brand than the positive information. This effect is understood as a habituation of Peruvians towards the positive contextual information about their group, and an ingroup bias that acts when their national identity is threatened by the negative input. This bias guides them towards explicitly favoring a product they consider related to their social identity. On the other hand, the lack of visible results on the implicit attitudes is explained by the order effect of the Implicit Attitudes Test (IAT). These findings are relevant for advertising and marketing industries in Peru, which constantly develop campaigns that extol Peru and the Peruvian identity.